Mapping the terrain : trends and shared features in BA programs across Australia 2001-2008. - Gannaway, Deanne; Trent, Faith; Upton, Hayley; Price, Sarah (Australian Learning and Teaching Council, 2008)
Report from a project that aimed: To understand the nature and role of a Bachelor of Arts degree in contemporary Australia; To map the diverse Bachelor of Arts programs on offer in Australia between 2001-2008; To identify the major strengths, difficulties, capabilities and contributions of the program; and to provide rich base-line data on the nature and models of BAs to be accessible for future curriculum planning for arts faculties. This report summarises the key trends and commonalities evident between Bachelor of Arts programs and programs within the field of Arts currently offered across Australia